(untitled) (Bioscience Journal, 2016)
The main physiology and biochemistry metabolism including amino acids composition and gamma-aminobutyric acid (GABA) content of sorghum during 3-day germination period was investigated. Respiratory rate increased during germination. Protease activity, free amino acid and reducing sugar content increased with germination time. While moisture, protein, fat and starch content decreased, significantly. Meanwhile, amino acid composition redistributed and the relative content of essential amino acids increased except for leucine and valine. In addition, some nonessential amino acids content such as proline, glycine and histidine was largely enhanced by germination. GABA content increased about 3 folds after germination. Furthermore, combining tannin (the main anti-nutritional factor) was converted to be free and solvable. These results greatly suggest that germinated sorghum could be a functional food rich in GABA and other health-promoting nutrients.Â